2013
DOI: 10.1186/1743-7075-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction favorably impacts metabolic and immune/inflammatory profiles in obese mice but curcumin/piperine consumption adds no further benefit

Abstract: BackgroundObesity is associated with low-grade inflammation and impaired immune response. Caloric restriction (CR) has been shown to inhibit inflammatory response and enhance cell-mediated immune function. Curcumin, the bioactive phenolic component of turmeric spice, is proposed to have anti-obesity and anti-inflammation properties while piperine, another bioactive phenolic compound present in pepper spice, can enhance the bioavailability and efficacy of curcumin. This study sought to determine if curcumin cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 52 publications
(57 reference statements)
1
23
0
Order By: Relevance
“…Data (Control n = 9; exposed to BMOV n = 8) are expressed as means ± SEM; ⁄ P < 0.05 vs. control group). (Wang et al, 2013). Therefore, the lower caloric intake resulting from the ingestion of V might contribute to decreasing the production of reactive oxygen species (ROS) and proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Data (Control n = 9; exposed to BMOV n = 8) are expressed as means ± SEM; ⁄ P < 0.05 vs. control group). (Wang et al, 2013). Therefore, the lower caloric intake resulting from the ingestion of V might contribute to decreasing the production of reactive oxygen species (ROS) and proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in lean mass were small, ∼10%. One study showed that administration of piperine to mice during caloric restriction had no effect on a series of parameters (36). Thus, the main effect of piperine appears to be to mitigate fat gain during caloric overload.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic piperine derivative, piperonyl carboxylic ester, was used to examine blood fat reduction in experimental animals. The derivative, with its molecular structure containing 1 piperonyl, plays a significant role in reducing serum cholesterol, but its role in reducing TGs is not significant; the derivative containing 2 radicals plays a significant role in reducing cholesterol and TG, but its role in reducing cholesterol is less significant than the role of the derivative containing only 1 piperonyl (Wang et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%